THE PREDICTION OF VANCOMYCIN DOSING REGIMEN IN PATIENTS WITH NORMAL RENAL FUNCTION AND PATIENTS WITH AUGMENTED RENAL CLEARANCE USING POPULATION PHARMACOKINETICS MODEL AND MONTE CARLO SIMULATION METHOD AT BUDDHACHINARAJ PHITSANULOK HOSPITAL - Chindasu, Pimsai; Lucksiri, Aroonrut; Taesotikul, Suthinee (Thai Bulletin of Pharmaceutical Sciences, 2026)
Current literature reports the initial recommended dose of vancomycin may be inadequate to promptly achieve therapeutic concentration in patients with normal renal function, especially the ones with augmented renal clearance (ARC). Our objectives were to describe vancomycin pharmacokinetics and to propose optimal vancomycin dosage regimens that achieve the area under the curve to minimum inhibitory concentration ratio (AUC/MIC) of 400 to 600 in adult patients with normal renal function, including the ones with ARC. This retrospective study collected data from patients with an estimated glomerular filtration rate (eGFR) > 90 mL/min/1.73m2. Population pharmacokinetics (PPK) analysis was performed using Phoenix NLME. Monte Carlo simulation of the final PPK model using Certara Trial SimulatorTM was employed to explore vancomycin dosage regimens that achieve a target AUC/MIC of at least 70%. A total of 172 patients with 222 blood specimen collections were included in the analysis. Data were fitted to one-compartment model with first order rate of elimination. Body weight was the covariate that correlated with volume of distribution, whereas body weight, age, and creatinine clearance (CLcr) calculated by the Cockcroft-Gault equation correlated with vancomycin clearance. Simulation of study populations revealed a usual vancomycin dose, 15-20 mg/kg every 12 hours, could not reach the target AUC/MIC in patients with CLcr more than 90 mL/min. The following regimens were suggested to achieve the target AUC/MIC: 17.5 mg/kg every 8 hours for patients with CLcr of 90 to 130 mL/min and, either 20 mg/kg every 8 hours or 15 mg/kg every 6 hours for patients with CLcr greater than 130 mL/min and those with ARC. However, for patients with CLcr ≥130 mL/min, a higher dose or shorter dosing interval of vancomycin was necessary, along with therapeutic drug monitoring and requires further study.